2017
DOI: 10.1002/polb.24283
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the degree of ionization on the growth mechanism of poly(diallyldimethylammonium)/poly(acrylic acid) multilayers

Abstract: pH‐dependent growth laws of the mass coverage Γ(n) of poly(diallyldimethylammonium) chloride and poly(acrylic acid) (PAA) layer‐by‐layer films are analyzed by Quartz Crystal Microbalance‐D. (Attenuated Total Reflection)‐FTIR spectroscopy shows a degree of dissociation of acrylic acid groups in the films identical to that in solution. Apart from pH‐regimes of differently pronounced exponential and linear growth, the corresponding kinetics indicate pH‐dependent adsorption, reorganization, and diffusion processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 39 publications
5
31
0
Order By: Relevance
“…The LbL technique is driven by electrostatic forces and entropy which is due to the release of water and low-molecular-weight ions into the solution and was further established, inter alia, by Möhwald . The formation of the PEMs mainly depends on the properties of the solutions from which the layers are formed, such as ionic strength, pH value, temperature, and salt concentration. , Different research groups showed that with the increase of the salt concentration, the layers get much thicker due to the screening of the charges, followed by a coiling of the polymer chains before the adsorption process. Currently, the LbL technique is used to investigate different possibilities of applications such as coatings for water purification and separation membranes, drug delivery systems, and PEM capsules used as optical sensors or for applications in biological systems. A great deal of research is already published for polyelectrolyte systems such as poly­(diallyldimethylammonium chloride) (PDADMAC) and poly­(styrene sulfonate). In this study, we focus on the PEM system of PDADMAC and poly­(ethylene- alt -maleic acid) [P­(E- alt -MA), p K a1 = 3.8, p K a2 = 6.1] which combines a strong and a weak polyelectrolyte. Within the range of pH 3–6 in this study, the degree of dissociation of the polyanion changes and therefore leads to a different growth behavior due to its pH dependence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LbL technique is driven by electrostatic forces and entropy which is due to the release of water and low-molecular-weight ions into the solution and was further established, inter alia, by Möhwald . The formation of the PEMs mainly depends on the properties of the solutions from which the layers are formed, such as ionic strength, pH value, temperature, and salt concentration. , Different research groups showed that with the increase of the salt concentration, the layers get much thicker due to the screening of the charges, followed by a coiling of the polymer chains before the adsorption process. Currently, the LbL technique is used to investigate different possibilities of applications such as coatings for water purification and separation membranes, drug delivery systems, and PEM capsules used as optical sensors or for applications in biological systems. A great deal of research is already published for polyelectrolyte systems such as poly­(diallyldimethylammonium chloride) (PDADMAC) and poly­(styrene sulfonate). In this study, we focus on the PEM system of PDADMAC and poly­(ethylene- alt -maleic acid) [P­(E- alt -MA), p K a1 = 3.8, p K a2 = 6.1] which combines a strong and a weak polyelectrolyte. Within the range of pH 3–6 in this study, the degree of dissociation of the polyanion changes and therefore leads to a different growth behavior due to its pH dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Within the range of pH 3–6 in this study, the degree of dissociation of the polyanion changes and therefore leads to a different growth behavior due to its pH dependence. Here, we expect the buildup of thick layers around pH 4 where the degree of ionization is relatively low and the polyanion is highly protonated . Within this environment, the polymers tend to coil; thus, as a result, thicker layers should be monitored.…”
Section: Introductionmentioning
confidence: 99%
“…[20] The influence of different salts (phosphates, chlorides and nitrates) and polyelectrolyte molecular weight on formation and erosion of multilayers on silica surfaces was investigated by means of optical reflectometry method. [8] It was shown that at very low ionic strength (1 mM) regular build-up of multilayers is observed independent of the salt used.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness and mechanical strength of PEMs can be varied within a wide range, and typically vary between nm to several µm and between a few kPa to several MPa [2,3,4,5,6], respectively. This is possible by simply varying the number of deposited polyelectrolyte layers and/or intrinsic properties of polyelectrolytes, such as the charge density, molecular weight and structure [7,8,9,10,11,12,13]. Other factors can be employed to even induce post-preparative changes of the film properties: For example, the ionic strength and charge-to-size ratio of specific ions [14,15,16], pH stimulation [17,18,19], organic solvent [20] or inorganic/organic ions exposed to PEMs [21,22] have been shown to influence the thickness and mechanical strength of PEMs.…”
Section: Introductionmentioning
confidence: 99%